Quasi-Religions - Smith, John E. author. aut Link
VIII, 154 p.
Keywords: This fascinating book considers systems of belief and practice which are not religions in the full-blown sense, but which nevertheless affect human life in ways similar to the role played by the recognised religions. Professor Smith's thorough account compares the features which Humanism, Marxism and Nationalism share with recognised religions, analysing each in turn, and asks whether there is not always a threat of the demonic when any contingent reality - man, the economic order, or the state - is made absolute.